Parasitando a Cuca: metodologias ativas aplicadas ao estudo das parasitoses no Ensino Médio - Michelle Milene de Sousa (2020)
Parasitosis still being a worldwide major public health concern since millions of people are parasitized annually, yet. Many cases are asymptomatic and environmental, socioeconomic and social factors are relevant to the transmission and contamination of society. This situation can be aggravated by the lack or precariousness of basic sanitation, personal hygiene and the lack of effective public policies. This work aimed to evaluate the effect of a didactic sequence involving educational games applied to the study of parasites. For the study, investigative teaching methodologies applied to the study of parasitic diseases were adopted for high school students, allowing students to act as active and proactive subjects in the construction of knowledge. The research was developed in a public school for 80 students of the second year of high school, in the city of Divinópolis, MG. In the present study, a qualitative descriptive analysis was used. As a criterion for assessing knowledge acquisition, students answered a pre- and post-activity questionnaire. The students developed playful games to be used as relevant support tools in the teaching of parasites, this proved to be a strategy of motivation and interest for students that made learning more attractive, personal, effective, mainly because it emphasizes the cognitive aspect. The accomplishment of this work allows to conclude, that the active methodologies contributed in a positive way, respecting the limitations and difficulties found by the students. Therefore, the results showed that parasitology practices aroused greater interest and made classes more dynamic.